Empowering Community Welfare through BUMDes Strategies: Memberdayakan Kesejahteraan Masyarakat melalui Strategi BUMDes - Faridah, Umi; Ravita, Nur (Indonesian Journal of Law and Economics Review, 2024)
This qualitative case study investigates the financial management and operational strategies of Village-Owned Enterprises (BUMDes) in Kenongo Village, Sidoarjo, aiming to enhance community welfare. Through interviews, observation, and documentation, key challenges such as limited community involvement and adherence to management principles are identified. Results show that despite existing facilities, BUMDes face obstacles in optimizing their functions. The study underscores the importance of community engagement and adherence to management principles in BUMDes’ operations, suggesting implications for improving economic prospects and empowering local communities. Highlight: Limited Engagement: Community involvement impacts BUMDes’ effectiveness. Principle Adherence: Management principles influence BUMDes’ performance. Economic Boost: Enhanced BUMDes operations benefit local economic development. Keywoard: BUMDes, financial management, community welfare, case study, Sidoarjo.